Pusa Raunak - A high yielding round melon variety for spring summer season - Sureja, Amish K; Munshi, A D; Pandita, Vinod K (Indian Horticulture, 2022)
Pusa Raunak is an early improved variety of round melon for spring-summer season cultivation developed by IARI for National Capital Territory of Delhi. Apart from superior quality characters, it showed 64% higher yield over the National check variety Punjab Tinda.